Welcome to the (almost) digital hospital. - Weiss, G.
The author reports on the (almost) digital hospital in the cardiology ward at the brand new Georges Pompidou European Hospital in Paris. It is a medical ideal where everyday operations and record-keeping are carried out and maintained almost exclusively with computers. At the heart of this ambitious model is the electronic patient record. The idea behind it is to make all of a patient's medical reports, lab results, and images electronically available to clinicians, instantaneously, wherever they are. Also, with an electronic record as a base, software tools that increase the accuracy of treatment can be added to improve patient outcomes and reduce cost
Keywords: Georges Pompidou European Hospital; Paris; Digital hospital; Electronic patient record; Hospital information system; Online medical references; Record-keeping.